Factores de riesgo asociados al desarrollo del cáncer de riñón - Tinoco Piuri, Kelly Samanta (Machala : Universidad Técnica de Machala, 2018)
Introduction: Kidney cancer is responsible for 3-5% of all malignant tumors and is the deadliest of the urinary tract, the most common form being clear cell carcinoma. Affecting men more between the sixth and seventh decade of life. Annually around the world 300,000 men and women are diagnosed with kidney cancer and 150,000 fail. The incidence is higher in developed countries and less frequent in underdeveloped countries such as Latin America. In Ecuador this neoplasm ranks eighth in men and eleventh in women. Objective: To describe the most relevant updated data in the medical literature on the main risk factors associated with the development of kidney cancer. Methodology: The bibliographic search of several scientific articles was carried out in journals indexed and reviewed by academic peers, obtained from Pubmed, Medscape and Google Academic databases, published during the last 5 years, related to renal cancer. Conclusions: Over the last 5 years, obesity, smoking, high blood pressure and acquired cystic disease have been described in patients with chronic dialysis as well established factors linked to renal cancer. Other factors have decreased their incidence as; type 2 diabetes when controlling other comorbidities, moderate consumption of alcohol and fruits, vegetables together with physical activity. Carcinogenic chemical agents, poor dietary habits, constant use of aspirin, and other medications have been described as new risk factors with poorly established bases.
Introducción: El cáncer de riñón es responsable del 3-5% de todos los tumores malignos y es el más mortal de las vías urinarias, la forma más común es el carcinoma de células claras. Afectando más a los hombres entre la sexta y séptima década de la vida. Anualmente en todo el mundo 300.000 hombres y mujeres son diagnosticados con cáncer renal y 150.000 fallesen. La incidencia es mayor en países desarrollados y menos frecuentes en países subdesarrollados como Latinoamérica. En Ecuador esta neoplasia ocupa el octavo lugar en hombres y décimo primer lugar en mujeres. Objetivo: Describir los datos actualizados más relevantes en la literatura médica sobre los principales factores de riesgo asociados al desarrollo del cáncer de riñón. Metodología: Se realizó la búsqueda bibliográfica de diversos artículos científicos en revistas indexadas y revisadas por pares académicos, obtenidas de las bases de datos Pubmed, Medscape y Google Académico, publicados durante los últimos 5 años, relacionados con el cáncer renal. Conclusiones: En los últimos 5 años se describen la obesidad, tabaquismo, hipertensión arterial y enfermedad quística adquirida en pacientes con diálisis crónica como factores bien establecidos vinculados al cáncer renal. Otros factores han disminuido su incidencia como; la diabetes tipo 2 cuando se controlan otras comorbilidades, el consumo moderado de alcohol y las frutas, verduras junto a la actividad física. Agentes químicos carcinógenos, deficientes hábitos dietéticos, el uso constante de aspirina, y otros medicamentos, han sido descritos como nuevos factores de riesgo con bases poco establecidas.
Keywords: NEOPLASIA RENAL; FACTORES DE RIESGO; EPIDEMIOLOGIA; DIAGNOSTICO